High prevalence of sexually transmitted infections among women screened for a contraceptive intravaginal ring study, Kisumu, Kenya, 2014. (December 2018) - Oliver, Vincent O; Otieno, George; Gvetadze, Roman; Desai, Mitesh A; Makanga, Mumbi; Akelo, Victor; Gust, Deborah A; Nyagol, Beatrice; McLellan-Lemal, Eleanor
We assessed prevalence and correlates of bacterial vaginosis (BV) and sexually transmitted infections (STIs) including herpes simplex virus type 2 (HSV-2), gonorrhoea (GC), syphilis (SYP), Chlamydia (CT) and HIV among Kenyan women aged 18–34 years who were screened for a contraceptive intravaginal ring study. Women provided demographic, behavioural and medical information, and underwent medical evaluation, including a pelvic exam. We computed crude and adjusted prevalence ratio (aPR) and 95% confidence interval (CI) using log-binomial regression. Of 463 women screened, 457 provided laboratory specimens and were included in the analysis. The median age was 25 years, interquartile range (21–28), and 68.5% had completed primary or lower education. Overall, 72.2% tested positive for any STI or BV. Point prevalence was 55.6, 38.5, 3.9, 2.0, 4.6, and 14.7% for HSV-2, BV, GC, SYP, CT, and HIV, respectively. Co-infection with HSV-2, BV, and HIV occurred in 28 (6.1%) participants. Having ≥1 STI/BV was associated with younger age at first sex (≤13 versus 17–19 years, aPR=1.27, 95% CI 1.07–1.51), history of exchange sex (aPR = 2.05, 95% CI 1.07–3.92), sexual intercourse in the past seven days (aPR = 1.17, 95% CI 1.01–1.36), and older age (30–34 versus 18–24 years, aPR = 1.26, 95% CI 1.06–1.48). STI/BV diagnosis was less likely for women reporting one lifetime sexual partner compared to women with ≥4 lifetime sexual partners (aPR = 0.70, 95% CI 0.54–0.92). Combination prevention approaches (biomedical, behavioural, social, and structural) tailored to women with diverse risk profiles may help mitigate STI/BV prevalence in this setting.